The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10008-014-2493-0
|View full text |Cite
|
Sign up to set email alerts
|

PtIr–WO3 nanostructured alloy for electrocatalytic oxidation of ethylene glycol and ethanol

Abstract: In this article, we characterized tungsten oxide-decorated carbon-supported PtIr nanoparticles and tested it for the electrooxidation reactions of ethylene glycol and ethanol. Phase and morphological evaluation of the proposed electrocatalytic materials are investigated employing various characterization techniques including X-ray diffraction (XRD) and transmission electron microscopy (TEM). Electrochemical diagnostic measurements such as cyclic voltammetry, chronoamperometry, and linear sweep voltammetry reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…Therefore the dehydrogenation step is facilitated [259][260][261] (3) the oxophilic nature leads to the formation of adsorbed water or OH group at the interface between Pd and the WO 3 at a lower potential, which promotes the oxidative removal of CO from the Pd surface. [260,262,263] In fact, Rutkowska et al found that coating WO 3 nanorods (50-70 nm diameter, 5 micro meter length) with Pd resulted in an improved the catalytic activity of the Pd/WO nanoparticles compared to Pd black. In addition to the electronic effect and bifunctional effect, the presence of partially reduced WO 3 -y or tungsten bronze and WO 3 helps the adsorptive/desorptive phenomena or interfacial O 2 transfer to help CO oxidation.…”
Section: Pd Transition Metal Oxides Based Catalystsmentioning
confidence: 99%
“…Therefore the dehydrogenation step is facilitated [259][260][261] (3) the oxophilic nature leads to the formation of adsorbed water or OH group at the interface between Pd and the WO 3 at a lower potential, which promotes the oxidative removal of CO from the Pd surface. [260,262,263] In fact, Rutkowska et al found that coating WO 3 nanorods (50-70 nm diameter, 5 micro meter length) with Pd resulted in an improved the catalytic activity of the Pd/WO nanoparticles compared to Pd black. In addition to the electronic effect and bifunctional effect, the presence of partially reduced WO 3 -y or tungsten bronze and WO 3 helps the adsorptive/desorptive phenomena or interfacial O 2 transfer to help CO oxidation.…”
Section: Pd Transition Metal Oxides Based Catalystsmentioning
confidence: 99%
“…CO stripping and hydrogen underpotential deposition methods are widely used to determine the ECSA. 22,23 In this study, the ECSAs of PtIr@C and Pt@C catalysts were calculated at a scanning rate of 25 mV s À1 within 0.5 M H 2 SO 4 using the CO stripping method. CO stripping voltammograms of catalysts exposed to CO gas were performed for 15 min (Fig.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…When using a single-layer CO charge value of 420 mC cm À2 , the ECSAs of PtIr@C and Pt@C were calculated to be 20.23 cm 2 and 14.49 cm 2 , respectively, according to the CO peak area. 22,24 According to the ECSA results, it was found that the PtIr@C catalyst has higher CO tolerance and a higher ECSA than Pt@C. Besides, electrochemical impedance spectroscopy (EIS) measurements were performed to better understand the properties of PtIr@C and Pt@C catalysts. Measurements were performed in 1 M KOH solution and 1 M CH 3 OH in the frequency range of 10 kHz to 0.01 Hz as shown in Fig.…”
Section: Njc Papermentioning
confidence: 99%
“…Indeed, they are well‐known multifunctional materials for fuel cells, in which they are employed as electrocatalysts and supports . Oxygen‐deficient tungsten oxide based materials, known as tungsten bronzes, are catalysts for the electrochemical oxidation of C 2 –C 3 alcohols and hydrogen in acid media . Tungsten oxide bronzes have also been used as electrocatalysts for oxygen reduction, photocatalysts, and as efficient catalysts in the hydrogenation of linear and cyclic alkenes, nitroarenes, and unsaturated organosulfur compounds .…”
Section: Introductionmentioning
confidence: 99%